2009
DOI: 10.1109/tcsi.2008.925819
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Design of OTA-C Oscillators with Native Amplitude Limiting

Abstract: An analog sinusoidal oscillator usually involves some form of amplitude-limiting mechanism. We examine operationaltransconductance-amplifier (OTA) nonlinearity as a choice for amplitude limiting and develop a general theory for its use in OTA-capacitor (OTA-C) oscillators. We facilitate our theoretical discussion with an illustrative design example that we fabricated and tested.Index Terms-Nonlinear oscillators. I. OSCILLATOR DESIGN APPROACHEST HE SINUSOIDAL oscillator is a basic analog-circuit component in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Macromodeling, starting from an op-amp model in 1974 [31], looks to create a nonlinear model to reproduce circuit responses as close as possible [32] using simpler digital numerical models. Models look to utilize generalized, low-order polynomials around a single fixed operating point [33][34][35][36][37], and some models utilize the nonlinear dynamics of the transistors [29,[38][39][40]. These techniques often are coupled with tool design approach, particularly joint verification of digital and analog systems [41][42][43][44].…”
Section: Level = 2: Enabling Circuit Designers To Build Level = 1 Blocksmentioning
confidence: 99%
“…Macromodeling, starting from an op-amp model in 1974 [31], looks to create a nonlinear model to reproduce circuit responses as close as possible [32] using simpler digital numerical models. Models look to utilize generalized, low-order polynomials around a single fixed operating point [33][34][35][36][37], and some models utilize the nonlinear dynamics of the transistors [29,[38][39][40]. These techniques often are coupled with tool design approach, particularly joint verification of digital and analog systems [41][42][43][44].…”
Section: Level = 2: Enabling Circuit Designers To Build Level = 1 Blocksmentioning
confidence: 99%
“…Operational transconductor amplifiers (OTAs)‐based oscillators using only capacitors (OTA‐Cs) or using resistance capacitance (RC) elements (OTA‐RC) have been widely investigated because of the availability of electronic tunability of the oscillation frequency in such oscillators, for instance see [1–32] and the references cited therein. In [33], it was shown that corresponding to any given single‐OTA‐RC sinusoidal oscillator, there are three other structurally distinct equivalent forms [having the same characteristic equation (CE)] one of which employs both grounded capacitors (GC) as preferred for IC implementation [34].…”
Section: Introductionmentioning
confidence: 99%
“…Some quadrature oscillators are also reported based on current feedback amplifier (CFA) [23] and CDTA [24] with external resistors. The theory of an OTA-C oscillator with native amplitude limiting was introduced without discussion in highfrequency operation [25]. A single CFA oscillator was reported to synthesise various functions including oscillation, but many passive components are required without the electronic tuning feature [26].…”
Section: Introductionmentioning
confidence: 99%